Accelerated atomic-scale exploration of phase evolution in compositionally complex materials. Issue 1 (15th December 2017) - Li, Y. J.; Savan, A.; Kostka, A.; Stein, H. S.; Ludwig, A.
Abstract : Combining nanoscale-tip arrays with combinatorial thin film deposition and processing as well as direct atomic-scale characterization (APT and TEM) enables accelerated exploration of the temperature- and environment-dependent phase evolution in multinary materials systems. Abstract : Combining nanoscale-tip arrays with combinatorial thin film deposition and processing as well as direct atomic-scale characterization (APT and TEM) enables accelerated exploration of the temperature- and environment-dependent phase evolution in multinary materials systems. Results from nanocrystalline CrMnFeCoNi show that this alloy is unstable and already decomposes after 1 h at low temperatures of around 300 °C. The combinatorial processing platform approach is extendible to explore oxidation and corrosion in complex structural and functional materials on the atomic scale.